Stateczność Ruchu Prętów Wirujących ze Zmienna Prędkością - Bogusz, W. (Engineering Transactions, 1958)
The problem considered is that of a bar rotating with sinusoidallyvariable angular velocity. The solution of the equation of motion is obtained by means of Bessel functions. From an analysis of this solution it follows that for a fluctuating velocity there exist, besides the critical velocities, other velocities, for which the motion is not stable. The term «dynamic critical velocities» is in this paper, used for these velocities.From the solution of the equation of motion it follows also that thestability of motion of a bar rotating with variable angular velocity depends on the frequency of velocity fluctuations and not on their amplitude.